Mechanical and viscoelastic properties of a temperature-responsive photocurable resin for 3D printed orthodontic clear aligners - Jin Young Choi; Hoon Kim; Seong Hun Kim; Su Jung Kim; Jung-Yul Cha; Se Yeon Lee; Jiho Lee; Jinhong Min; Sunho Jang; Tanveer Ahmed Khan; Hyun-Joong Kim; Ki Beom Kim (Scientific Reports)
Abstract This study investigates the mechanical and viscoelastic properties of TC-85, a biocompatible material specifically designed for orthodontic applications, with a focus on how temperature variations influence its mechanical and viscoelastic properties and their relevance to clinical outcomes. Using a Digital Light Processing (DLP) 3D printer, the photosensitive resin TC-85 is printed, and extensive thermo-mechanical testing is conducted, which includes evaluations of tensile modulus, stress relaxation, and creep behavior. Dynamic Mechanical Analysis (DMA) is conducted at temperatures varying from 30 to 45 °C to assess the material’s adaptive response to thermal fluctuations. TC-85 is distinguished by its unique mechanical properties, which include a temperature-sensitive stiffness, stress relaxation capability, and shape memory feature. The results demonstrate that TC-85 maintains an enhanced level of residual force and a faster recovery of strain through numerous cycles of loading and unloading. At 40 °C, TC-85 displays a substantial reduction in its storage modulus, while maintaining consistent strain recovery and volumetric constancy. The study highlights TC-85’s potential in orthodontic treatments, providing adaptable mechanical and viscoelastic properties that enable the exertion of consistent and regulated forces on teeth. Its resistance to force decay, stable volume at raised temperatures, and shape memory properties enhance hygienic maintenance and patient comfort, positioning TC-85 as a pioneering material for the next generation of clear aligners.